Development of a micro-accretion process for three dimensional structures - Yeo, Swee Hock. (2008)
The development of microsystem technology has initiated various types of microfabrication processes. These processes in turn serve as a platform for the development of new improved processes with increasingly higher fabrication resolution, This work reports on an investigative study on Localized Electrochemical Deposition (LECD) - a new 3-D rapid direct fabrication process capable of producing high aspect ration microstructures. This process uses the principles of electrodeposition but as its name indicates, localization of the electric field that induces the deposition, holds the key to its capability for fabrication with high feature resolution. Nickel microstructures were electrochemically deposited on copper cathodes from nickel sulphamate plating solution using a non-soluble microelectrode as the anode. The growth characteristics of the deposited structures were studied in terms of the deposition rate, dimensional control and the degree of porosity. The novelty of the work reported here lies in: 1. The use of pulsed voltage to deposit structures in LECD and subsequently reduce their porosity 2. The use of electrode rotation for improved dimensional control 3. The use of electrode tip concavity to increase feature resolution. 4. The development of flexible tooling system based on wire electro-discharge grinding technique for fabricating varied electrode diameters